The Implementation of Nurses’ Safety during the Covid-19 Pandemic based on Work Stress - Puguh Widiyanto; Sri Hananto Ponco Nugroho (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Nurses’ safety is one of the prominent issues during the COVID-19 pandemic. The pandemic has also given psychological effects to nurses especially work stress. This research aimed to investigate the relationship between work stress and the implementation of nurses’ safety. This was a descriptive correlational study with a cross-sectional approach. The samples were 134 nurses in a hospital in Magelang Regency who were obtained by purposive sampling. The data were gathered through DASS 21 questionnaire and a questionnaire on nurses’ safety practices during the COVID-19 pandemic. Then, the data were analyzed by the Spearman rank tests. The results indicated that there was a significant relationship between work stress and the implementation of nurses’ safety (p= 0.000). Nurses who had normal work stress implemented nurses’ safety properly.Abstrak: Keselamatan perawat merupakan salah satu isu penting dalam masa pandemi Covid-19. Masa pandemi Covid-19 juga memberikan dampak psikologis pada perawat terutama stres kerja. Penelitian ini bertujuan mengetahui hubungan stres kerja dengan pelaksanaan keselamatan perawat. Desain penelitian yang digunakan adalah korelasi deskriptif dengan pendekatan cross sectional. Teknik pengambilan sampel menggunakan purposive sampling dengan jumlah sampel sebanyak 134 perawat di sebuah rumah sakit di Kabupaten Magelang. Pengambilan data menggunakan instrumen kuesioner Depression, Anxiety, and Stress Scale (DASS 21) dan kuesioner pelaksanaan keselamatan diri perawat pada masa pandemic Covid-19. Selanjutnya di analisis menggunaan uji rank spearman. Hasil penelitian menunjukkan ada hubungan bermakna antara stres kerja dengan pelaksanaan keselamatan perawat (p= 0,000). Perawat yang memiliki tingkat stres kerja normal ditemukan melaksanakan keselamatan perawat dengan baik.